2022
DOI: 10.1002/chem.202202104
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Research of Photo‐Assisted Lithium‐Based Rechargeable Batteries

Abstract: The application of solar energy is crucial for alleviating the energy crisis and achieving sustainable development. In recent years, photo‐assisted rechargeable batteries have attracted researchers because they can directly convert and store solar energy in the batteries. And it also can be used like a normal battery without light illumination. Photo‐assisted lithium‐based batteries have received more attention than other energy storage systems due to their higher energy density and relatively mature developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 137 publications
(101 reference statements)
0
10
0
Order By: Relevance
“…Note that for all these reported battery designs no pure photocharging is possible, since photoexcited electrons do not have a larger potential than the very negative electrode potential of M x + /M. We recommend the following reviews for the interested reader to dive further into this exciting research field. , …”
Section: A Brief Overview Of Current Solar Battery Conceptsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that for all these reported battery designs no pure photocharging is possible, since photoexcited electrons do not have a larger potential than the very negative electrode potential of M x + /M. We recommend the following reviews for the interested reader to dive further into this exciting research field. , …”
Section: A Brief Overview Of Current Solar Battery Conceptsmentioning
confidence: 99%
“…However, recently the field of solar batteries has moved toward a single material performing both light absorption and charge storage. While this design presents the highest level of integration, it is simultaneously the most difficult and comes with both conceptual and practical challenges. ,,,, This is because a material must function both as a light absorber and as a mixed electronic–ionic conductor (MIEC) to harvest light, shuttle electronic charges, and store ionic chargescomplex photophysical effects which must occur simultaneously. Bifunctional materials exist for both cathodes and anodes, although by far, more exist for cathodes than for anodes.…”
Section: A Brief Overview Of Current Solar Battery Conceptsmentioning
confidence: 99%
“…13 Unlike integrated solar batteries, coupled solar batteries that couple photoelectric conversion unit and electrochemical redox unit at one photoelectrochemical storage electrode can enable direct and flexible solar energy storage, making it potentially applicable to a variety of fields, such as electric vehicles, mobile/ portable electronic devices, and many other areas. 1,8,20,21,[30][31][32][33][34] Several studies have explored the concept of coupled solar batteries, inspired by a related work in 1976 that utilized a three-electrode battery configuration, 35 with a S/S 2À cathode, an Ag 2 S/Ag anode, and a polycrystalline CdSe photoelectrode. However, this approach was limited by issues such as toxicity, complex device structure, high cost, and low energy conversion efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…To date, ZIBs have gradually attracted the attention of researchers. In addition, the researchers have suggested that the use of light-assisted materials in batteries can directly introduce light into batteries and reduce energy loss in many intermediate conversion processes [ 18 ]. In 2018, Dai et al reported the development of a photo-assisted zinc-air battery using a photo-responsive dual-function ORR/OER electrocatalyst [ 19 ].…”
Section: Introductionmentioning
confidence: 99%